A Reliability optimization of a coupled soil structure interaction applied to an offshore wind turbine. (August 2021) - Kamel, A.; Dammak, K.; Yangui, M.; Hami, A. El; Jdidia, M. Ben; Hammami, L.; Haddar, M.
Abstract: In this paper, a dynamic analysis of an offshore wind turbine (OWT) considering soil structure interaction (SSI) is performed. The design of these highly expensive structures tends to find the best compromise between cost and safety. To do so, a coupling between reliability-based design optimization and the numerical model of the OWT is required. An extension of some RBDO methods such as the Optimum Safety Factor (OSF), Hybrid Method (HM) in the case of an OWT considering SSI is then proposed. Based on the efficiency of these methods, the Robust Hybrid Method (RHM) is then applied to overcome the drawbacks of the current methods. By comparing it results to the classical ones, the advantages and the efficiency of the RHM is then presented. The effects of the SSI on the optimal configuration is then discussed. Finally, the RHM is applied to an improoved wind turbine model containig 18 design variables to determine the optimal structural configuration of a 2 MW OWT.